The Economic Consequences of Accounting for Stock Splits and Large Stock Dividends - Peterson, Craig A.; Millar, James A.; Rimbey, James N. (The Accounting Review, 1996)
[Prior studies of stock dividends and stock splits have failed to provide valid tests of earnings signaling because they incorrectly assume that "stock splits" do not restrict future cash dividends. Unlike previous studies, which also incorrectly assume that cash dividends are limited only to the amount of retained earnings, we present a study based on actual accounting treatment and appropriate statutory definitions of distributable equity. We find that more positive information is signaled if the stock distribution accounting choice reduces distributable equity.]